Analisis Kajian Sosiolinguistik Campur Kode Dalam Film Pendek “Tilik 2018” - Ningrum, Wahyu; Sagita, Anisa Rahma; Fitriani, Ni’matul Maula; Satiti, Tara Cantika Candra; Neina, Qurrota Ayu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of code mixing is a form of one of the language variations that occurs generally in the lives of bilingual and multilingual communities, including in Indonesia. Films as a representation of social life often reflect the use of code mixing in dialogues between characters. The purpose of this study is to study and find the forms and types of code mixing in the short film Tilik (2018) and to identify the factors behind its use. This study uses a qualitative descriptive approach with a sociolinguistic approach. By watching the film carefully and taking notes on the dialogue to analyze the code mixing contained therein, then the data is collected. The analysis was carried out based on the code mixing theory put forward by Suwito (1985), which divides code mixing into insertion (word insertion), alternation (code replacement), and congruent lexicalization (lexical integration). The results of the research data show that the code mixing elements in the Tilik film are used as a communication strategy that reflects social closeness between characters, shows cultural identity, and creates a humorous effect. Factors that can influence the code mixing used in this film include social, situational, and cultural background factors of the characters involved in the conversation. It is hoped that this research will help sociolinguistic studies, especially in understanding how language variation is used in film media as a reflection of language dynamics in society.